Helping managers to more effectively delegate authority. Issue 6 (8th August 2016) - Lyons, Paul R.
Abstract : Purpose: The purpose of this paper is to provide human resources (HR) practitioners with some information and tools to assist managers become more effective delegators of authority. Included is information that might be used in a training session for managers. Design/methodology/approach: Drawn from research and opinion is information that serves to help managers form solid partnerships with employees in sharing of some tasks and responsibilities. Several findings from research aim to illuminate key prescriptions for effective delegation. A survey instrument is provided to assist managers assess their own preferences in delegation practices. Findings: Findings clear the fact that delegation can be deliberately planned and executed. There are several areas that can be assessed to ultimately guide a manager in effective delegation. Originality/value: The originality of this paper lies in its potential to: a) assist and guide a manager as he/she goes about establishing an effective delegation; and b) the arrangement of the content of the paper to enable HR practitioners to use the material as a training module for managers.